2015
DOI: 10.1038/bmt.2014.327
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after autologous SCT in lymphoma patients grouped by weight

Abstract: Obesity continues to be an increasing global health issue contributing to the complexity of chemotherapy dosing in the field of SCT. Investigation into the optimal dosing weight used to calculate chemotherapy doses in obese patients undergoing SCT is limited and inconclusive. Our single-center, retrospective study compared safety and efficacy outcomes by body mass index (BMI) for 476 adult lymphoma patients who underwent auto-SCT with a myeloablative chemotherapeutic regimen of BU, CY and etoposide dosed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…Others have suggested that severe obesity is a poor prognostic factor for hematopoietic transplantation [17], yet this and another recent study using appropriate dose adjustments failed to show increased risk of serious complications for the severely obese treated with autologous HCT [18]. There are significant differences between our study and other reports.…”
Section: Discussioncontrasting
confidence: 86%
“…Others have suggested that severe obesity is a poor prognostic factor for hematopoietic transplantation [17], yet this and another recent study using appropriate dose adjustments failed to show increased risk of serious complications for the severely obese treated with autologous HCT [18]. There are significant differences between our study and other reports.…”
Section: Discussioncontrasting
confidence: 86%
“…On a similar note, studies investigating the impact of obesity on AHCT outcomes are heterogeneous with different results . Two large studies from the Center for International Blood and Marrow Transplant Research (CIBMTR) that have looked at AHCT outcomes of large cohorts of patients with lymphoma and myeloma showed comparable results .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Studies evaluating transplant outcomes and survival of obese patients have had mixed findings with large cohort studies showing at least similar outcomes to normal-weight patients. [5][6][7][8][9][10][11][12][13] Several factors leading to poor peripheral blood hematopoietic progenitor cell (HPC) mobilization have been reported. [14][15][16][17][18] A potentially significant, yet understudied factor is obesity, which may have a bearing on HPC mobilization via its effect on the interaction of the hematopoietic stem cell niche and its microenvironment, the need for a higher CD34+ cell dose based on actual body weight and alteration of mobilization agent pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary malignancy, a potential long-term toxicity that might be expected to increase with increasing doses of chemotherapy, showed no significant differences associated with weight in 5-year cumulative incidence, and there was no development of any unique type of malignancy. 14 No specific anatomical or molecular markers of post-transplant residual tumor mass are available to determine specific antitumor effects of adjusted weight antitumor therapy. However, as the relapse rates in the three weight groups, at 1, 3 and 5 years, were not significantly different, these results suggest the probability that the increased drug dose associated with obesity was at least as effective in attaining the same degree of tumor control as the more standard dose given to normal weight patients.…”
mentioning
confidence: 99%
“…In fact, obese patients who presumably received the highest amounts of chemotherapeutic agents showed a decrease in 100-day mortality relative to normal or overweight patients, but no significant difference in relapse-free survival or OS. 14 In this single-center, retrospective study of the safety and efficacy of auto-SCT in 476 adult lymphoma patients, all drugs were dosed on the basis of Adj BW in which 25% of the difference between TBW and IBW was added to the patient's IBW to determine Adj BW (Adj BW = IBW+0.25 (TBW − IBW)), which was then used as the basis for dose calculations.…”
mentioning
confidence: 99%